Characterisation of running specific prostheses and its effect on sprinting performance - Grobler, L. (2015)
The development of the running specific prosthetic (RSP) has allowed athletes with lower limb amputations to participate at a high level in sports such as sprinting. Literature regarding mechanical properties of RSPs and their influence on the athlete`s performance, on the other hand, is limited. This makes prosthetic selection a difficult task. The aim of this study was to assess the biomechanical and physiological effects of the mechanical characteristics of different RSPs on an athlete`s sprinting performance. The sprint performances of athletes with lower limb amputations were described in a retrospective analysis of Olympic and Paralympic times between 1992 and 2012, in an attempt to assess whether the technological advances in RSPs is evident. A 14 - 26% performance improvement was found for the T42 and T44 classes of the 100 and 200 m during this time in comparison to 2.2 - 2.8% for the Olympic athlete performances. These results were further supported by the lower competition density found in the amputee groups (Olympic 23.90 and 9.29 competitors.s-1; T42 4.53 and 1.93 competitors.s-1). It was therefore proposed that technology played a significant role in the performance progression of these athletes over the last 20 years. Differences in the characteristics of two RSP models (model E and X) were investigated. This was achieved by athlete independent mechanical testing during which the RSPs were dropped from a height of 30 cm and left to bounce on a force platform. The results revealed differences in the peak ground reaction force (GRFpeak) (model E > model X; p < 0.05) and maximal RSP compression (?L) (model X > model E; p < 0.05). This indicated that the RSP model E is more stiffness than the model X. These stiffness characteristics related to discrepancies in sprinting economy of an athlete completing four maximal anaerobic running tests (MART) using different RSPs. Two RSP stiffness categories of each model (Ecat4, Ecat6, Xcat4, Xcat6) were used for this testing and was randomly allocated to each testing session. It was found that the running speed at which the athlete attained a blood lactate concentration of 10 mmol.l-1 was the highest with the stiffest RSP (Ecat6), whereas it was the lowest in the softest RSP (Xcat4). Accordingly the lowest functional muscular fatigue as measured by a decrease in the pre and post-test counter movement jump height was found in this condition (Ecat6 7.35% vs. Xcat4 24.43%). From these investigations it was clear that technology is an important factor in the performances of amputee sprint athletes. Therefore prosthetic selection is of the utmost importance. Differences in the mechanical characteristics of the RSPs influence the sprint physiology and biomechanics and should therefore be taken into consideration when selecting a RSP.